Knowledge of personal and environmental factors as predictors of coronary heart diseases among non- academic staff of higher institutions in Abeokuta, Ogun State. (2011)
Background: The scourge of coronary heart diseases is an increasing phenomenon worldwide. It is a challenge that has posed a greater risk on the health of people of both the developed and developing countries. The purpose of this study was to determine the knowledge of personal and environmental factors as predictors of coronary heart diseases among non-academic staff of higher Institutions in Abeokuta Ogun State Nigeria. Methods: Descriptive survey research design was used for the study.lt was delimited to non-academic staff of higher institutions in Abeokuta, Ogun State Nigeria. One thousand (1000) samples were randomly selected within the total population of the study. A self developed structured questionnaire was used as instrument for data collection, a reliability coefficient of 0.74 was obtained. Data were analyzed using SPSS. Version 14. Regression statistical techniques were applied to test hypotheses at 0.05 level of significant. Result: Four hypotheses were gathered, tested and analyzed using descriptive statistics of frequency counts, bar charts, pie chart and regression to test ail hypothèses at 0.05 alpha level of significance. It was fmd out based on the results of fmdings that âge, sex and genetic that are non-modifiable factors predisposing coronary heart disease produced F,(3/996)=l 1.2%, P< .05 while modifiable factors of physical inactivity, diet and alcoholism significantly predisposed the development of coronary heart disease, levels F,(3/996)= 11.511, P< .05. Environmental factors of work environment, inaccessibility of recreational facilities, inavailability of high-quality cafeteria significantly predisposed the development of coronary heart disease. F, (3/996) =12.624, P< .05. The results also showed the relative contributions of all the variables in the development of coronary heart disease F, (9/990) =7.204, P< .05 Conclusions: According to the fmdings, it was recommended that there should be a national flag off of the awareness on prevention of Coronary Heart Disease as it is one of the major killer of sudden death, there should be a quarterly seminar for the non- academic staff of higher institution on the knowledge of coronary heart disease as well as the risk factors that predisposed people to this condition